Programming the tomato genome with LED light - Grundy, Steven (2019)
Light quality has a profound effect on many aspects of plant growth and development. An extremely important breakthrough has been made with light-emitting diode (LED) technology which now is playing an increasing role in horticultural lighting. A key feature is that the spectral output of LEDs can be adjusted, which makes it possible to intercept light at high efficiency and drive photosynthesis to produce adequate crop yield and quality. The LEDs lighting opens up tremendous opportunities for researchers, farmers, and breeders. Currently, the effects of different LED light on plant growth, especially, on morphological and physiological changes in different crops have been studied. However, very little is known about the regulatory mechanisms and correlations between these changes at the omics level by integrative systems biology approach. In this study, the influence of light quality on yield, morphology, pigment metabolism and photosynthetic performance was evaluated in Solanum lycopersicum cv. Micro-Tom. Transcriptomic analysis (RNA-Seq) and gene co-expression networks have been conducted to identify differentially expressed genes and key genes regulated by light quality. Growing Micro-Tom from germination to harvest under red (R), blue (B), red/blue (RB), or red/blue/green (RBG) LED lights, as well as fluorescent tube (Fl) lighting, the R spectrum produced plants with shade-avoidance type growth, with significantly increased height, elongated petioles, a reduction of photosynthesis, and a reduction in yield and fruit soluble sugar content compared to RB and RBG grown plants. The transcriptomic analysis shows that Fl drastically altered the transcriptome compared to any LED light spectra, with 6623, 8805, and 5942 genes differentially expressed in pair-wise comparisons between Fl with R, B, and RBG, respectively, and 3528 genes commonly differentially expressed between all LED comparisons. Between R, B, and RBG. In R transcriptome, the expression of RvB and RvRBG differentially expressed genes, the expression of growth promoting hormone biosynthesis and signalling genes was enhanced, as well as the expression of cell-wall modifying enzymes and transcription factors which regulate growth. Additionally, plants grown under R had reduced photosynthetic and pigment related gene expression, while plants grown under B had reduced expression of defense, biotic stress-responsive genes, and a reactive oxygen species signalling gene. The resultant co-expression network included 17 co-expression modules, of which 9 genes were associated with the biosynthesis of anthocyanin. Anthocyanin biosynthesis genes were co-expressed together, along with a known transcription factor ANTHOCYANINLESS and an APETELAa ERF transcription factor, with zero expression of these genes in B, low levels in R, and high expression in RBG. Twelve differentially expressed genes were identified from the RNA-Seq study as candidate genes of interest for gene functional studies. To further validate the regulation of these genes by light, RNA was harvest weekly from Micro-Tom plant grown under the same light qualities, and a qRT-PCR time-course of gene expression of these genes was conducted to establish which genes are consistently differentially regulated by light. Five genes were found to be consistently differentially regulated by light: a cellwall modifying gene XYLOGLUCAN ENOTRANSGLUCOSYLASE HYDROLASE 16, cytokinin catabolic gene CYTOKININ DEHYDROGENASE/KINASE 6, a C2H2 transcription factor, a MYB-RELATED transcription factor, and HAT4 BZIP transcription factor. In the future, the function of these genes will be studied through Agrobacterium-mediated gene silencing in Micro-Tom. Additionally, a second RNASeq experiment studying the effect of supplemental green LED light added to a background of RB, which was found to induce an early transcriptional response with 1190 genes differentially expressed. However, this response was transient, as after one day and seven days 305 and 270 genes were differentially expressed, respectively. These data provide a basis for understanding light signalling in tomato, and the extensive transcriptional reprogramming which underpins the adaptive response of tomato morphology, biochemistry, and development in response to spectral quality. The observation of the effects of LED spectra on the transcriptome as well as the effect of LED spectra on yield in tomato are novel and have a meaningful consequence for the identification of molecular markers which regulate important plant traits, which can be targeted for improved crop yield and quality.